Problems in defining the motor space of children - Šekeljić Goran V.; Marković Jovan M. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
The aim of the study is to define the structure of motor abilities on the selected sample and compare the obtained model with the model determined by nine motor abilities. Testing was performed on a sample of 220 girls and 180 boys aged 10, using a battery of 18 motor tests. Based on the results obtained, factor analysis determined 5 vectors in the boys' group and 4 vectors in the girls' group, carrying the most information about the measured characteristics. For a certain number of variables, it was found that they do not belong to any constituted vector. The results indicate differences in the structure of the motor space between the obtained and tested model; differences in the structure of the motor space between girls and boys; and a greater number of hypothetical models that can explain the structure of the motor space in children. The research results contribute to a better understanding of structural theories in the field of motor abilities; they point out deficiencies in the scientific methodology dealing with the study of motor space and its structure; and indicate the necessity of an interdisciplinary anthropological approach to solve this problem.